A Trust and Priority Based Code Updated Approach to Guarantee Security for Vehicles Network - Xiao Liu; Wei Liu; Yuxin Liu; Houbing Song; Anfeng Liu; Xuxun Liu (IEEE Access, 2018)
With the development of smart equipment and technologies, vehicular networks (VNs) are expected to have wide-range applications in intelligent transportation system services. The software code in these devices often contains bugs that can be remotely exploited by attackers, so gathering software vulnerabilities information and updating program codes timely in those devices are crucial for network security. To improve the security of VN, a Complete Software Update based on Trust and Priority (CSUTP) scheme is proposed. The scheme includes two processes: one is the process of collecting status information of program codes from devices to data centers and another is the process of disseminating program codes from data centers to devices. When collecting status information of program codes, mobile vehicles pick up the status information with higher priority due to the limited storage space. Furthermore, mobile vehicles can also disseminate the status information to data centers though another mobile vehicles which is with higher trust. Thus, the success arrival ratio and the coverage ratio of collecting status information of program codes are improved. In the process of dissemination program codes, data centers select the mobile vehicles with higher trust and higher coverage ratio to disseminate program codes. The comprehensive experimental results indicate that the performance of CSUTP scheme is better than the random program codes diffusion and collection scheme (RPCDC). The CSUTP scheme increases data coverage ratio by 25%-86.67% and success arrival ratio by 52.119%-93.65%. The ratio of data redundancy in the CSUTP scheme to the RPCDC scheme is about 54.07%-62.061%, and the ratio of dissemination delay in the CSUTP scheme to the RPCDC scheme is about 80.854%-91.492%.